Multiscale finite element musculoskeletal model for intact knee dynamics. (February 2022) - Shu, Liming; Yamamoto, Ko; Yoshizaki, Reina; Yao, Jiang; Sato, Takashi; Sugita, Naohiko
Abstract: Background and objective: The dynamic characteristics of the intact knee joint are valuable for treating knee osteoarthritis and designing knee prostheses. However, it remains a challenge to elucidate the detailed dynamics of the knee due to its complexity of anatomical structure and complex interaction with body dynamics. Methods: In this study, a unique subject-specific musculoskeletal model with a concurrent high-accuracy intact finite element knee model was created and used to simultaneously evaluate the kinematics and mechanics of an intact knee joint during the gait cycle. Results: A medial pivot motion with external rotation, and a large parallel anterior translation were observed in the stance and swing phases, respectively, which is consistent with the in vivo fluoroscopy measurements. The maximum axial contact force on the knee joint, observed at 45% of the gait cycle, is approximately 2.89 times the body weight. The medial cartilage bears 65.7% of the total axial contact force. The results demonstrate that the cartilage–cartilage contact bears most of the joint load (62.5%) compared to the cartilage–meniscus–cartilage contact (37.5%). Regarding contact mechanics, the maximum contact pressure on both sides of the tibial cartilage (8.2 MPa) is almost similar to the first axial loading peak (14%) of the gait cycle. Additionally, the maximum contact pressure (6.01 MPa) was observed during the stance phase of the gait cycle on the patellofemoral joint. Conclusions: The predicted results on the tibiofemoral and patellofemoral joints provide a theoretical basis for the treatment of knee joint diseases and knee prosthesis design. Moreover, this approach presents a comprehensive tool to evaluate the mechanics at both the body and tissue levels. Therefore, it has a high potential for application in human biomechanics. Highlights: A finite element musculoskeletal modeling approach was proposed, which is able to evaluate the mechanics at both the body and tissue levels. The study provides a theoretical basis of intact knee mechanics for the treatment of knee joint diseases and knee prosthesis design. The cartilage-cartilage contact bears most of the knee joint loads during the gait cycle.